2016
DOI: 10.1007/s11814-015-0255-z
|View full text |Cite
|
Sign up to set email alerts
|

Artificial neural networks as classification and diagnostic tools for lymph node-negative breast cancers

Abstract: Artificial neural networks (ANNs) can be used to develop a technique to classify lymph node negative breast cancer that is prone to distant metastases based on gene expression signatures. The neural network used is a multilayered feed forward network that employs back propagation algorithm. Once trained with DNA microarraybased gene expression profiles of genes that were predictive of distant metastasis recurrence of lymph node negative breast cancer, the ANNs became capable of correctly classifying all sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 24 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…The number of specimens obtained is small, and the source of the mass tissue cannot be further characterized. Therefore, it is believed that the results of thick-needle aspiration biopsy are more useful in the diagnosis of breast lesions than fine-needle aspiration cytology [ 1 ]. Huynh et al compared the differences in the ultrasound appearance of the two groups of lesions, and the analysis suggested that there is an underestimated ultrasound appearance of precancerous lesions [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The number of specimens obtained is small, and the source of the mass tissue cannot be further characterized. Therefore, it is believed that the results of thick-needle aspiration biopsy are more useful in the diagnosis of breast lesions than fine-needle aspiration cytology [ 1 ]. Huynh et al compared the differences in the ultrasound appearance of the two groups of lesions, and the analysis suggested that there is an underestimated ultrasound appearance of precancerous lesions [ 2 ].…”
Section: Introductionmentioning
confidence: 99%